Awareness Program of Pesticides Used among Farmers using Difficulty-Usefulness Pyramid (A Suggestion for Health Laws and Policies Regarding the Use of Pesticides) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pesticides are toxic chemical substances that are used in agriculture to control plant pests. Excessive use ofpesticides and uncontrolled can cause negative effects among farmers, such as vomiting, diarrhea, dyspnea,blurred vision, paresthesia, slurred speech, and chest pain. The prevention effort through health educationwas used to prevent the risk behavior of farmer, however, it still found obstacles. There are many elementsneed to be improved and it must be selected which element that significant and priority to change riskbehavior among farmers. This study had selected the elements based on Difficulty-Usefulness Pyramid(DUP). The sample was 100 respondents who knew about pesticides in Indonesia. Personal protectiveequipment (PPE), storage of pesticides, procedure for using pesticides, use of pesticide doses, duration andfrequency of spraying pesticides, cleaning the equipment, spraying pesticides based on the wind direction,time of pesticide spraying were selected elements in this study. Difficulty and usefulness were indicators todetermine the priority of attributes. Attribute scale (1 to 10) was used based on the level of importance ineach attribute. Google form questionnaire was used to collect the data. Each element was measured by: (1)difficulty and usefulness; (2) the mean score of difficulty and the mean score of usefulness; (3) range (frommean score of difficulty to mean score of usefulness). Then the range was sorted starting from the smallestand presented in the form of a pyramid. The pyramid showed that the priority elements were use of pesticidedoses, procedures for using pesticides, personal protective equipment (PPE), cleaning the equipment, timespraying pesticides, duration and frequency of spraying pesticides, storage of pesticides, spraying pesticidebased on the wind direction.